Práticas e formações de professores de matemática no ensino remoto: letramento digital como desafio no pós-pandemia - FREITAS, Claúdio Lopes de (Universidade Federal de Mato Grosso, 2022)
The COVID-19 pandemic context became an opportune moment to debate technological training of teachers and the practice of teaching in virtual environments. Thus, study aim was to highlight learning and teaching aspects and teachers’ digital literacy who taught mathematics in Basic Education during emergency remote teaching. This is characterized as exploratory research, with convenience and non probability sampling, following a mixed approach, with qualitative and quantitative data. Data collection took place with the application of digital questionnaires for mathematics teachers who performed remote teaching activities, in school year 2020 and part of 2021. Answers were obtained from 70 teachers. Results emphasizes the use of several strategies by teachers to face remote education demands, as well as their own investments to purchase equipment. Low digital literacy of most teachers was faced with an autonomic search for qualification and adherence to the packages of large technology companies, underlining the absence of departments and educational institutions in training for remote classes. It is concluded that the remote teaching of mathematics was, many times, a solitary teacher’ challenge, assuming the financial and formative burden to obtain some success. Despite individual efforts, digital teaching literacy still imposes itself as a political agenda to be faced in the post-pandemic.